Fibrocytes in early and long-standing rheumatoid arthritis: a 6-month trial with repeated synovial biopsy, imaging and lung function test. Issue 1 (5th March 2021) - Just, Søren Andreas; Nielsen, Christian; Werlinrud, Jens Christian; Larsen, Pia Veldt; Hejbøl, Eva Kildall; Tenstad, Helene Broch; Daa Schrøder, Henrik; Barington, Torben; Torfing, Trine; Humby, Frances; Lindegaard, Hanne
Abstract : Objectives: To correlate the level of fibrocytes in peripheral blood, synovial tissue and in vitro culture in rheumatoid arthritis (RA) with changes in disease activity, imaging and pulmonary function. Methods: Twenty patients with early RA (ERA) and 20 patients with long-standing RA (LRA) were enrolled in a 6-month prospective study. Sixteen patients undergoing wrist arthroscopy were healthy controls. Patients with RA underwent pulmonary function tests, ultrasound and synovial ultrasound-guided needle biopsy of the same wrist at baseline and 6 months. Wrist MRI was performed at baseline (all) and 6 months (ERA). Circulating fibrocytes were measured by flow cytometry, in vitro by the number of monocytes that were differentiated to fibrocytes and in synovial biopsies by counting in histological sections. Results: Fibrocytes were primarily located around vessels and in the subintimal area in the synovium. Fibrocyte levels did not decline during the trial despite effective RA treatment. In the ERA group, increased synovitis assessed by ultrasound was moderate and strongly correlated with an increase in circulating and synovial fibrocyte levels, respectively. Increased synovitis assessed by MRI during the trial in the ERA group was moderately correlated with both increased numbers of circulating and cultured fibrocytes. Absolute diffusion capacity level was overall weakly negatively correlated with the level of circulating and synovial fibrocytes. The decline in diffusion capacity during the trial was moderately correlated with increased levels of synovial fibrocytes. Conclusion: Our findings suggest that fibrocytes are involved in RA pathogenesis, both in the synovium and the reduction in lung function seen in a part of patients with RA. Trial registration number: NCT02652299 .